Growth, theoretical, optical and dielectric properties of a semi-organic zinc acetate picolinium succinate (ZAPS) single crystals for nonlinear optical applications. (2022) - Chinnasamy, E.; Deepa, K.; Senthil, S.
Abstract: Nonlinear optical material Zinc Picolinate dihydrate (ZPD) was synthesized by slow evaporation solution growth technique. The grown crystals were characterised by Single crystal X-ray diffraction analysis. The presence of functional groups in the grown crystal was analyzed using FT-IR spectrum. The UV–vis spectrum shows a low absorption in the entire visible region. Optical band gap of the grown crystal was found to be 4.46 eV. The evaluation of optical constants by employing UV–visible absorbance data such as, reflectance, extinction coefficient, refractive index, are supportive towards good performance as NLO devices. The nonlinear optical behavior from the non-centrosymmetric crystal was observed by the generation of frequency doubled (2ω) optical radiation when subjected to pulsed Nd:YAG laser (1064 nm, 10 ns, 10 Hz) using Kurtz-Perry method.